Peran Keluarga dalam Membangun Karakter Anak: Studi Deskriptif di Pondok Pesantren Farishul Qur’an - Khafi, Achmad; Muhajir, Ahmad; Yasin, Muhammad (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2024)
Character education is an important process in forming character and morals. In the family context, character education plays a major role because the family is the first role model for children in developing potential and building character. This research aims to explore how to educate personal and family character and describe the aspects that need to be considered in family character education in order to achieve harmony in the household. This research uses a qualitative descriptive approach with observation methods, semi-structured interviews and documentation. Data collection was carried out through direct experience of researchers at the Farishul Qur'an Islamic Boarding School. The results of the research show that the process of character formation in the family can start with the habit of positive attitudes and providing good role models for children. The findings also indicate that integration between the roles of children, parents and the environment is very necessary to ensure the success of character education in the family.